A Comparative Phytochemical Analysis of Choorna and Bhavitha Choorna of Apamarga (Achyranthes aspera Linn.) - Babu, Aleena V; Ansary, P Y; oommen, Sara Monsy; Shincymol , V V (International Research Journal of Ayurveda & Yoga, 2021)
Samskara is a pharmaceutical process which aids in the transformation of the inherent attributes of a dravya which provides to the addition of a new property in them. The samskara or the processing helps in the qualitative and quantitative alterations to the improvement, intensification, modification and lowering the unwanted effects of the substance. Bhavana is one mode of samskara in which the powdered drugs are soaked in an appropriate Drava (liquid medium like Swarasa, Kashaya etc.). Dravya is kept completely immersed in drava or it is triturated in drava for specific time period. The drug Apamarga (Achyranthes aspera Linn.) is selected as the drug of choice for the purpose of bhavana. The phytoconstituents present in the drug determines its efficacy. As the bhavana can amplify the efficacy of a drug the present study aimed to compare the findings of phytochemical analysis of both the choorna and bhavitha choorna of the drug. The tannin, fiber, phenol content and extractive values obtained for the bhavitha choorna was found more than that obtained for the choorna indicating quantitative enhancement of phytoconstituents which substantiate the fact that process of bhavana will help to increase the potency and efficacy of a drug.